Copper supported on functionalized MCM-41 as a novel and a powerful heterogeneous nanocatalyst for the synthesis of benzothiazoles. (15th January 2019) - Noroozi Pesyan, Nader; Batmani, Hana; Havasi, Forugh
Graphical abstract: A new functionalized mesoporous catalyst (Cu(II)-Glycerol/MCM-41) has been synthesized as a highly efficient heterogeneous nanocatalyst for the synthesis of Benzothiazols derivatives. Abstract: A new functionalized mesoporous catalyst (Cu(II)-Glycerol/MCM-41) has been synthesized as a highly efficient heterogeneous nanocatalyst for the synthesis of benzothiazoles derivatives. Powder XRD, TGA, TEM, SEM, EDX, BET, FT-IR and ICP-OES techniques are employed to characterize the prepared nanocatalyst. These one-pot reactions were carried out under green and mild reaction conditions in EtOH as a green solvent and the catalyst can be reused up to 5 consecutive cycles without significant change in its catalytic activity.